Comparison of two bond strength testing methodologies for bilayered all-ceramics - Dundar, Mine; Ozcan, Mutlu; Gokce, Bulent; Comlekoglu, Erhan; Leite, Fabiola; Valandro, Luiz Felipe (Elsevier B.V., 2007)
Objectives. This study compared the shear bond strength (SBS) and microtensile (MTBS) testing methodologies for core and veneering ceramics in four types of all-ceramic systems.Methods. Four different ceramic veneer/core combinations, three of which were feldspathic and the other a fluor-apatite to their respectively corresponding cores, namely leucitereinforced ceramic ((IPS)Empress, Ivoclar), low leucite-reinforced ceramic (Finesse, Ceramco), glass-infiltrated alumina (In-Ceram Alumina, Vita) and lithium disilicate ((IPS)Empress 2, Ivoclar) were used for SBS and MTBS tests. Ceramic cores (N = 40, n = 10/group for SBS test method, N=5blocks/group for MTBS test method) were fabricated according to the manufacturers' instructions (for SBS: thickness, 3 mm; diameter, 5 mm and for MTBS: 10 mm x 10 mm x 2 mm) and ultrasonically cleaned. The veneering ceramics (thickness: 2 mm) were vibrated and condensed in stainless steel moulds and fired onto the core ceramic materials. After trying the specimens in the mould for minor adjustments, they were again ultrasonically cleaned and embedded in PMMA. The specimens were stored in distilled water at 37 degrees C for 1 week and bond strength tests were performed in universal testing machines (cross-head speed: 1mm/min). The bond strengths (MPa +/- S.D.) and modes of failures were recorded.Results. Significant difference between the two test methods and all-ceramic types were observed (P < 0.05) (2-way ANOVA, Tukey's test and Bonferroni). The mean SBS values for veneering ceramic to lithium disilicate was significantly higher (41 +/- 8 MPa) than those to low leucite (28 +/- 4 MPa), glass-infiltrated (26 +/- 4 MPa) and leucite-reinforced (23 +/- 3 MPa) ceramics, while the mean MTBS for low leucite ceramic was significantly higher (15 +/- 2 MPa) than those of leucite (12 +/- 2 MPa), glass-infiltrated (9 +/- 1 MPa) and lithium disilicate ceramic (9 +/- 1 MPa) (ANOVA, P < 0.05).Significance. Both the testing methodology and the differences in chemical compositions of the core and veneering ceramics influenced the bond strength between the core and veneering ceramic in bilayered all-ceramic systems. (c) 2006 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: all-ceramics; bond strength; core-veneer ceramic; microtensile test; shear test